The association between endometriosis and female infertility: a literature review - Duarte, Amanda Nunes (2021)
Endometriosis is a chronic disease that affects about 20% of women in fertile age caused by implants of endometrial tissue located outside the uterine cavity, especially in places such as the ovaries and peritoneal cavity. The origin of this condition remains unknown and there are several theories in literature that aim to explain the pathophysiology involved, such as Sampson’s Theory, known as retrograde menstruation theory. The disease has two main outcomes: pelvic pain and infertility. The difficulty in spontaneous conception is related to the local inflammatory response generated by ectopic endometrial cells, which leads to increased levels ofcytokines, interleukins, growth factors, angiogenic factors and defense cells. This environment can alter physiological mechanisms involved in ovulation, fertilization and implantation, in addition to impairing the quality of sperm and promoting anatomical changes in the female genital tract. The present study aimed to gather the existing data in the contemporary literature to understand the mechanisms involved in the infertility caused by endometriosis. Thus, it was concluded that inflammation is the mainevent for all the processes involved that are able to influence fertility and that studies on the subject raise expectations for the development of new approaches for these patients.